Metformin reduces glycometabolism of papillary thyroid carcinoma in vitro and in vivo. (January 2017) - Shen, Chen-Tian; Wei, Wei-Jun; Qiu, Zhong-Ling; Song, Hong-Jun; Zhang, Xin-Yun; Sun, Zhen-Kui; Luo, Quan-Yong
Abstract : More aggressive thyroid cancer cells show a higher activity of glycometabolism. Targeting cancer cell metabolism has emerged as a novel approach to prevent or treat malignant tumors. Glucose metabolism regulation effect of metformin in papillary thyroid cancer was investigated in the current study. Human papillary thyroid carcinoma (PTC) cell lines BCPAP and KTC1 were used. Cell viability was detected by CCK8 assay. Glucose uptake and relative gene expression were measured in metformin (0–10 mM for 48 h)-treated cells by 18 F-FDG uptake assay and western blotting analysis, respectively. MicroPET/CT imaging was performed to detect 18 F-FDG uptake in vivo . After treatment with metformin at 0, 2.5, 5 and 10 mM for 48 h, the ratio of p-AMPK to total AMPK showed significant rising in a dose-dependent manner in both BCPAP and KTC1, whereas p-AKT and p-mTOR expression level were downregulated. 18 F-FDG uptake reduced after metformin treatment in a dose-dependent manner, corresponding to the reduced expression level of HK2 and GLUT1 in vitro . Xenograft model of PTC using BCPAP cells was achieved successfully. MicroPET/CT imaging showed that in vivo 18 F-FDG uptake decreased after treatment with metformin. Immunohistochemistry staining further confirmed the reduction of HK2 and GLUT1 expression in the tumor tissue of metformin-treated PTC xenograft model. In conclusion, metformin could reduce glucose metabolism of PTC in vitro and in vivo . Metformin, by targeting glycometabolism of cancer cells, could be a promising adjuvant therapy alternative in the treatment modality of advanced thyroid carcinoma.